"Not My Proudest Moment": Guilt, Regret, and the Coming-Out Narrative. (1st March 2019) - Gutterman, Lauren Jae
Abstract: This article draws on oral history interviews with twenty-six lesbian and bisexual women who came out within the context of heterosexual marriages between the 1970s and the early 2000s. Despite the extent to which the LGBTQ community emphasizes narratives of progress and triumph, feelings of shame, guilt, regret, and ambivalence figured significantly in these women's life stories, particularly with regard to their experiences of coming out. This article thus considers how oral history can provide queer narrators with an opportunity to share negative feelings that often remain unspoken within mainstream LGBTQ culture and politics.